Pengaruh Komitmen Pegawai dan Kualitas Pelayanan Publik terhadap Kinerja, Kepuasan Konsumen, dan Kepercayaan Masyarakat - Eliza, Mutia; Eka, M. S. Idrus; Troena, Afnan; Setiawan, Margono (Jurnal Aplikasi Manajemen, 2011)
This study aimed to test the effect of employee commitment and quality of public services 10 employee performance, customer satisfaction and public confidence. The findings showed that: 1). the commitment of employees (x1) significantly affects the quality of service (x2), 2). commitment of employees (x1) significantly affects performance (v1) with marked positive path coefficient, 3). commitment of employees (xl) influential significant effect on community satisfaction (y2). 4). Commitment of employees (x1) non significant effect on trust in the community (Y3), 5). quality of service (x2) significantly affects performance (v1), 6). Quality of service (x2) significantly affects community satisfaction (v2), 7). quality of service (x2) significantly affects people's satisfaction (Y3), 8). performance (yl) significantly affects people's confidence (y2). 9). performance (v1) significantly affects people's confidence (Y3). 10). community satisfaction (42) significantly affects people's confidence (Y3).